2008
DOI: 10.1021/ie800064z
|View full text |Cite
|
Sign up to set email alerts
|

Study of I/I2 Poisoning of Fe2O3-Based Catalysts for the H2SO4 Decomposition in the Sulfur−iodine Cycle for Hydrogen Production

Abstract: The poisoning effect of I -/I 2 mixtures on ferrous oxide based catalysts was investigated. These catalysts were used in the sulfuric acid thermal decomposition that is the highest endothermic step in the sulfur-iodine thermochemical cycle for hydrogen production by water splitting. This decomposition reaction needs a temperature as high as 1100 K to occur with a convenient thermodynamic yield for SO 2 formation, and it is affected by kinetic limitations. Therefore only the use of a suitable catalyst allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In previous literatures, various evaluations of the SO 3 conversion thermodynamic can be found [3,8,15,[21][22][23][24][25][26][27]. The systematic studies of SO 3 decomposition show the equilibrium conversion ratio is influenced by pressure and temperature dramatically; thus, the partial pressure of gaseous SO 3 in the reactor needs to be carefully considered when a thermodynamic curve is obtained [3,4,24,25]. The CuO-CeO 2 complex oxides catalyst has been widely used in multiple processes, such as water-gas shift reaction [28], SO 2 adsorption [29], and oxidation of CO or methanol [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous literatures, various evaluations of the SO 3 conversion thermodynamic can be found [3,8,15,[21][22][23][24][25][26][27]. The systematic studies of SO 3 decomposition show the equilibrium conversion ratio is influenced by pressure and temperature dramatically; thus, the partial pressure of gaseous SO 3 in the reactor needs to be carefully considered when a thermodynamic curve is obtained [3,4,24,25]. The CuO-CeO 2 complex oxides catalyst has been widely used in multiple processes, such as water-gas shift reaction [28], SO 2 adsorption [29], and oxidation of CO or methanol [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the activities of various catalysts, the thermodynamic data are thus needed to know the maximum SO 3 conversion ratio. In previous literatures, various evaluations of the SO 3 conversion thermodynamic can be found . The systematic studies of SO 3 decomposition show the equilibrium conversion ratio is influenced by pressure and temperature dramatically; thus, the partial pressure of gaseous SO 3 in the reactor needs to be carefully considered when a thermodynamic curve is obtained .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that copper pyrovanadate (Cu 2 V 2 O 7 ) is an efficient catalyst for SO 3 decomposition below 650 °C, 8 temperatures at which most conventional oxide catalysts are less active and less stable. [9][10][11][12][13][14][15][16][17][18] The combination of the pyrovanadate (V 2 O 7 2− ) framework, which is resistant to sulfate formation, and a copper redox species achieves both catalytic activity and stability. The catalytic activity can be enhanced by supporting the catalyst on 3-D mesoporous SiO 2 followed by thermal aging above the melting point of Cu 2 V 2 O 7 (>780 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Because NSs and NPs did not show any ORR catalytic activity in H 2 SO 4 (data not shown), ORR in alkaline and neutral pHs is reported in this study. The possible reason for the noncatalytic activity of NS and NP in H 2 SO 4 might be surface poisoning by sulfate ions. The ORR catalytic activities analyzed in KOH and PBS solutions using cyclic voltammograms (CVs) at 10 mV/s scan rate are plotted in Figure a,b, respectively. Figure a clearly shows an anodic shift in the ORR onset potentials of NS and NP in comparison to carbon nanotubes (CNTs), which are close to the Pt/C in KOH solutions (see Figure S5); however, the onset potentials of NS, NP, and CNT are almost similar as the pH decreased to 7.0 (Figure b), indicating the influence of pH on the catalytic activity of VSe 2 .…”
Section: Resultsmentioning
confidence: 99%